The students’ Readiness for E-Learning during Covid-19 in North Maluku - Firmansyah Firmansyah; Magvirah Octasary; Irmawaty Hasyim; Yetty Yetty (Institut Agama Islam Negeri Palopo, 2023)
The objective of this study was to assess the E-learning readiness of the students in Maluku Utara. The present study used descriptive quantitative in design, aimed to examine the level of E-learning readiness among the students. From three bachelor subgroups, participants were selected using stratified random sampling. Students who had attended virtual classrooms for at least one semester during the Covid-19 Pandemic met the selection criteria. The results showed that during Covid-19 pandemic 59% of the students had ready for E-learning 34,2% neutral and 6,8% were not ready. Most of the participants had provided in internet access, devices used were available and the method used during online class were easy to adapt. The results also evidenced that the students supported two factors